BUSINESS DEVELOPMENT STRATEGY FOR CATFISH REARING AT CIRCULAR TANK IN GUNUNGKIDUL, YOGYAKARTA PROVINCE: STRATEGI PENGEMBANGAN BISNIS PEMBESARAN IKAN LELE KOLAM BUNDAR DI GUNUNGKIDUL, DAERAH ISTIMEWA YOGYAKARTA - Sholikhah, Anna Nafiah Karimatus; Muhaimin, Abdul Wahib; Maulidah, Silvana; Koestiono, Djoko; Tjahjono, Agus (Jurnal Teknologi Perikanan dan Kelautan, 2026)
The fisheries sector plays an important and potential role in the Indonesian economy. The fisheries business in Indonesia is divided into three subsectors, i.e., capture fisheries, aquaculture, and processing. The Mina Mulya Maju Mandiri (4M) Cooperative is a fisheries cooperative engaged in production cooperatives (breeding, rearing, marketing, and procurement of fisheries facilities and infrastructure) and savings and loan cooperatives located in Kapanewon Semin, Gunungkidul Regency, Yogyakarta Special Region. The 4M Cooperative has a community of aquaculture members who run catfish farming businesses under the guidance and supervision of the cooperative. The purpose of this study is to formulate a strategy for developing catfish farming in circular ponds by identifying internal and external factors, business planning with a SWOT analysis, and analyzing business development strategies to be implemented. This study used a descriptive research method with qualitative and quantitative data. Data sources in this study consisted of primary and secondary data obtained from scientific journals, previous research reports, and the Central Statistics Agency (BPS) of Gunungkidul Regency and Yogyakarta Special Region. Data collection methods were carried out through observation, documentation, and interviews. The results of the study show that the business position is in quadrant I (aggressive) with SO (strengths and opportunities) strategic steps to formulate a strategy for developing a circular tank catfish farming business at the Mina Mulya Maju Mandiri Cooperative (4M).